A Reconsideration of the English Sources of La coronación de la señora Gracisla - Joseph J. Gwara (Medievalia, 2018)
In response to a study by Louise M. Haywood, Joseph J. Gwara challenges her interpretation of La coronación de la señora Gracisla, an anonymous work discovered in 1976, as a defense of Catherine of Aragon’s virginity and hence an implicit justification for her second marriage to Henry VIII of England. Rejecting this hypothesis, Gwara attributes the work to Juan de Flores, viewing it as a juvenile divertissement written c. 1475 to celebrate the engagement of Leonor de Acuña and Pedro Alvarez Osorio, both members of the Castilian aristocratic elite. This interpretation of Gracisla is based on a detailed analysis of stylistic, codicological, genealogical, and historical evidence.